P82 Evaluation of the LENT and PROMISE score for malignant pleural mesothelioma by histological subtype. (12th November 2019) - Banka, R; Ferris, R; Hung, A; Gkogkou, P; Mishra, E
Abstract : Introduction: The LENT and PROMISE scores are prognostic scores developed to predict prognosis in patients with malignant pleural effusions (MPE) including mesothelioma. Previous work has demonstrated that the LENT score underestimates survival in subtypes of patients with lung adenocarcinoma. Aim: To evaluate the LENT and clinical PROMISE score in a cohort of patients presenting with MPE secondary to mesothelioma (MPM) by histological subtype. Methods: Records were retrospectively reviewed from January 1, 2011- December 31, 2018 and January 1, 2013 – December 31, 2018 for patients with non-epithelioid and epithelioid mesothelioma respectively who presented with MPE. Patients who were alive at the time of data analysis were included for PROMISE score analysis only. Only patients with complete data available to calculate LENT/PROMISE score were included in analysis. Results: 142 patients were diagnosed with MPE and MPM. Complete data was available to analyse LENT and PROMISE score in 99 and 136 patients respectively. The overall median survival (n=122) was 315 days (IQR 167–538). The median survival was significantly different for different histological subtypes: sarcomatoid, (n=27) 191 days (IQR 120–349); biphasic (n=21) 282 days (IQR 135–473); and epithelioid (n=70) 481 days (IQR 236–620)(p=0.008). Most patients with sarcomatoid MPE had a low risk LENT score despite poor survival (table 1). The PROMISE score did not differentiate between patients with MPM, with 121/136 (89%) scoring 0–20 (3 month mortality <25%) (table 1). Conclusion: In our sample, patients divided into significantly different survival groups based on histology. The LENT score misclassified sarcomatoid MPM patients as being in a low mortality group. The PROMISE score failed to differentiate between patients with MPM. References: Clive, et al . Thorax 2014;69(12):1098–1104. Psallidas, et al . Lancet Oncol 2018;19(7):930–939. Abisheganaden J, et al . Respiration 2018;96(4):308–313.